CASE STUDY OF THE CAUSES OF FAILURE OF COMBINATION OF GABION AND GEOTEXTILE CONSTRUCTION TO HANDLE LANDSLIDES ON THE SLOPE OF KARIANGAU SUBSTATION, BALIKPAPAN, EAST BORNEO - Desy Rahmadania; Rusdiansyah Rusdiansyah (Universitas Lambung Mangkurat, 2022)
The slope of the GI Kariangau, Balikpapan, East Kalimantan uses a combination of gabion and geotextile construction to handle landslides on the slopes. However, there was a failure that indicated deformation of the gabion reinforcement and damage to the geotextile sheet. The failure of the reinforcement was caused by a landslide on the slope. This design begins with the collection of the necessary secondary data. Then proceed to calculate the stability of the gabion reinforcement at each level. This was followed by modeling the slope using the Geo5 2020 slope stability demo version program to get the safety factor value. Analysis of the program was carried out under various conditions, namely slopes before and after reinforcement, excavation at the foot of the slopes, and variations in groundwater level. From the results of the analysis, the value of the slope safety factor before and after being reinforced was 5.46 and 5.76. An increase in the value of the safety factor before and after the reinforcement of gabions shows that gabions play a role in increasing slope stability. The value of the slope safety factor before and after the landslide was 5.46 and 0.78. The decrease in the value of the slope safety factor before and after excavation activities shows that excavation has an effect on reducing the value of slope stability but is still within safe limits. Rain conditions affect reducing the value of soil parameters so that it affects the strength of the slopes. The failure of the combined construction of gabion reinforcement and geotextiles was caused by a decrease in the value of the shear strength of the soil due to saturated soil conditions in the gabion reinforcement area.